Green Logistics: Environmental Impact Assessment of Intelligent Logistics Automation - Shengtao Lin (Journal of World Economy, 2025)
With the rapid development of the logistics industry, intelligent logistics automation technology has emerged and been widely applied in various logistics processes, and its environmental impacts have increasingly attracted attention. This study focuses on intelligent logistics automation technology and systematically and comprehensively evaluates its multidimensional environmental impacts, including key areas such as energy consumption, resource utilization, waste emissions, and ecosystem impacts. Through an in-depth analysis of the application of intelligent logistics automation technology in real logistics scenarios and a quantitative analysis of its performance in improving energy efficiency, optimizing resource allocation, and reducing waste emissions, this study reveals its potential positive and negative environmental effects. Meanwhile, this study emphasizes the application effects of green logistics strategies in intelligent logistics automation and analyzes how to integrate the green concept into the planning, design, implementation, and operation of intelligent logistics automation systems.